2017
DOI: 10.1200/jco.2017.35.15_suppl.6589
|View full text |Cite
|
Sign up to set email alerts
|

Concordance assessment of a cognitive computing system in Thailand.

Abstract: 6589 Background: IBM Watson for Oncology (WFO) was trained by Memorial Sloan Kettering and is a cognitive computing system that uses natural language processing to ingest patient data in structured and unstructured formats. The system provides physicians with treatment options that are derived from established guidelines, the medical literature, and training from patient cases. In this study, we assessed the degree of concordance between treatment recommendations proposed by WFO and oncologists at Bumrungrad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…A observational study from Korea showed a 73% concordance rate for colon cancer and a 49% concordance rate for gastric cancer (Somashekhar et al, 2016;Suwanvecho et al, 2017). And, a comparative Study from Korea indicated that WFO without the gene expression assay has limited clinical utility (Kim et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A observational study from Korea showed a 73% concordance rate for colon cancer and a 49% concordance rate for gastric cancer (Somashekhar et al, 2016;Suwanvecho et al, 2017). And, a comparative Study from Korea indicated that WFO without the gene expression assay has limited clinical utility (Kim et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…12 Consistency of treatment regimens between WFO and oncologists had been observed for breast cancer, lung cancer, gastric cancer, colon cancer, rectal cancer, cervical cancer, and ovarian cancer. 12,[15][16][17] However, the concordance varies significantly according to different countries and cancer types. 12,[15][16][17] There are many guidelines for NSCLC precise therapies.…”
Section: Introductionmentioning
confidence: 99%
“…12,[15][16][17] However, the concordance varies significantly according to different countries and cancer types. 12,[15][16][17] There are many guidelines for NSCLC precise therapies. The commonly used clinical guidelines include the ASCO (American Society of Clinical Oncology) lung cancer guideline, National Comprehensive Cancer Network (NCCN) Clinical Practice guideline, European Society of Cancer Internal Medicine (ESMO) guideline, and Chinese Society of Clinical Oncology (CSCO) guideline.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison studies of WfO against recommendations at a tumor board in India noted concordance in 93% of breast, 96.4% of lung, 81.0% of colon and 92.7% of rectal cancer cases . A review in Thailand noted concordance rates of 89% for colorectal, 91% for lung, 76% for breast, and 78% for gastric cancer, with variance often driven by regional guidelines . An expansion of the 2016 Thailand study conducted in 2017 for a total of 590 cases found the overall concordance rate for the retrospective cases was 81%; 78% for bladder, 70% for breast, 56% for cervical, 90% for colon, 82% for gastric, 93% for lung, 79% for ovarian, 82% for prostate and 94% for rectal.…”
Section: Introductionmentioning
confidence: 99%